1978
DOI: 10.1021/bi00604a032
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the microsomal mixed function oxidase system: redox properties of detergent-solubilized NADPH-cytochrome P-450 reductase

Abstract: Hepatic microsomal NADPH-cytochrome P-450 reductase was solubilized from rabbit liver microsomes in the presence of detergents and purified to homogeneity by column chromatography. The purified reductase had a molecular weight of 78 000 and contained 1 mol each of FAD and FMN per mol of enzyme. On reduction with NADPH in the presence of molecular oxygen, an 02-stable semiquinone containing one flavin free radical per two flavins was formed, in agreement with previous work on purified trypsin-solubilized reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 21 publications
5
33
0
Order By: Relevance
“…We found no changes in the electron-spin relaxation time compared to the power dependence of the ESR saturation properties of the protease-treated and detergent-solubilized forms of the P-450 reductase. The same observations have been made by Iyanagi et al [42].…”
Section: Discussionsupporting
confidence: 84%
“…We found no changes in the electron-spin relaxation time compared to the power dependence of the ESR saturation properties of the protease-treated and detergent-solubilized forms of the P-450 reductase. The same observations have been made by Iyanagi et al [42].…”
Section: Discussionsupporting
confidence: 84%
“…The A2771A456 ratio for the rabbit liver reductase is 7.4 as compared with 8.7 for the rat liver reductase (13) and 6.7 and 6.3 for the rat liver enzyme solubilized by treatment with bromelain (41) or trypsin (42), respectively. The minimal molecular weight of the rabbit liver microsomal reductase was estimated from the flavin content to be 77,000; this figure is in reasonable agreement with the value of 78,000 reported by Iyanagi et al (17) and 74,000 determined by calibrated SDS-polyacrylamide gel electrophoresis in the present study.…”
supporting
confidence: 93%
“…The availability of the highly purified reductase as well as two forms of cytochrome P-450 (14,15) from a single source will permit more meaningful studies on the interactions of these enzymes in the reconstituted system (16). While this paper was in preparation, Iyanagi et al (17) reported the extensive purification and some of the properties of the rabbit liver reductase. The reductase is unusual in containing both FMN and FAD, as first reported for trypsin-solubilized preparations (18) and confirmed for the de-tergent-solubilized enzyme purified from both rat (10)(11)(12)(13) and rabbit liver microsomes (9,17).…”
mentioning
confidence: 99%
“…The molecular weights of the human and rabbit proteins were 77 500 and 76 500, respectively. While the molecular weight of the human enzyme is 3500 higher than that reported by Guengerich et al (1981), the molecular weight of the rabbit reductase compares favourably with other values in the literature (Vermillion &Coon 1974;Iyanagi et al 1978;Black & Coon 1982). In this study the human reductase was purified in the presence of phenylmethylsulfonyl fluoride and the appearance of lower molecular weight fragments due to proteolysis was avoided (Guengerich et al 198 1).…”
Section: Discussionsupporting
confidence: 73%